The cultural front. The laboring of American culture in the twentieth century - Denning, Michael (London, 2010)
"A panoramic history of the culture of Depression-era America and the Popular Front. The Cultural Front charts the extraordinary upsurge of cultural activity and theory in America that began during the Great Depression and embraced Disney animators and proletarian novelists alike, alongside Orson Welles, Duke Ellington, John Dos Passos, C. L. R James and Billie Holiday. Spawned by the Popular Front of the Communist Party, it grew to encompass virtually every aspect of high and popular art in the US, instigating one of the most culturally rich and exciting periods in American history."